Linking Peripartal Dynamics of Ruminal Microbiota to Dietary Changes and Production Parameters - Derakhshani, Hooman; Tun, Hein M.; Cardoso, Felipe C.; Plaizier, Jan C.; Khafipour, Ehsan; Loor, Juan J. (Frontiers in Microbiology, 2017)
During the peripartal period, proper acclimatization of rumen microorganisms to variations in nutritional management can facilitate the transition into lactation. This study characterized the temporal shifts in the composition and functional properties of rumen microbiota during the periparturient period in dairy cows subjected to a typical two-tiered feeding management approach. Ruminal digesta samples from eight multiparous fistulated Holstein cows were collected on days -14, -7, +10, +20 and +28 relative to parturition. High-throughput Illumina sequencing of the V4 region of the bacterial 16S rRNA gene revealed distinct clustering patterns between pre- and postpartal rumen microbiota. During the prepartal period, when the dry matter intake was at the lowest level, we observed strikingly lower inter-animal variations in the composition of the rumen microbiota. Genera Ruminococcus and Butyrivibrio, which are consisted of major fibrolytic rumen dwellers, were overrepresented in the prepartal rumen ecosystem. In contrast, increased postpartal DMI was associated with enrichment of bacterial genera that are mainly consisted of proteolytic, amylolytic, and lactate-producer species (including Prevotella, Streptococcus, and Lactobacillus). These, together with the postpartal enrichment of energy metabolism pathways, suggested a degree of acclimatization of the ruminal microbiota to harvest energy from the carbohydrate-dense lactation diet. In addition, correlations between rumen microbiota and parameters such as milk yield and milk composition, underscored the metabolic contribution of this microbial community to the cow's performance and production.